Distinct histological patterns in chronic hepatitis D with nucleos(t)ide analogue therapy - Hercun, Julian; Heller, Theo; Glenn, Jeffrey S.; Kleiner, David E.; Koh, Christopher (Frontiers in Medicine, 2023)
Background Chronic hepatitis delta virus (HDV) infection leads to a more severe hepatitis than hepatitis B virus (HBV) infection alone. Specific histological staining patterns have been described in HBV mono-infection, however this has not been extensively investigated in HDV co-infection. This study evaluated whether the use of nucleos(t)ide analogs (NAs) for concurrent HBV infection has an impact on the histological appearance of chronic HDV. Methods Liver biopsies of all patients referred for management of HDV infection were reviewed and hepatitis-specific stains for HBV antigens were evaluated. Clinical and histological characteristics were compared between patients on and off-NA therapy. Results 50 patients were included in our analysis, of which 26 (52%) were on NA therapy at the time of the biopsy. Overall, 8% stained for HBV core antigen and 86% stained for HBV surface antigen. On and off-NA groups had similar degrees of fibrosis and inflammation, however NA patients had an odds ratio of 7.15 for membranous staining and 0.13 for scattered granular staining (p = 0.001). No association was found with markers of disease severity or viral activity, with nonetheless a lower score of total inflammation noted in biopsies with a positive membranous stain (8.5 vs. 10.3 p = 0.04). Conclusion In chronic HDV infection, patients treated with nucleos(t)ide analogs demonstrate a unique membranous staining pattern for hepatitis B surface antigen, which is not associated with HBV or HDV replicative activity. These findings may help improve the understanding of the role of HBV directed therapy in HDV pathophysiology. Highlights Histological staining is associated with viral activity in chronic HBV, however this has been infrequently explored in HDV. In HDV, staining patterns differ based on HBV treatment status and do not appear to be associated with markers of viral activity.